Analisis Perbandingan Skeptisisme Profesional Mahasiswa Akuntansi: Studi Kasus Mahasiswa Akuntansi Fakultas Ekonomi Universitas Negeri Padang - Muthi'ah Gita Fajar; Vanica Serly (Universitas Negeri Padang, 2023)
This study aims to investigate the effectiveness of professional ethical course for accounting students at Faculty of Economic in Padang State University. Based on student participation in Business Ethics and Accounting Profession subject, we measure their Professional Skepticism using six factors who developed by Hurtt (2010) known as Hurtt’s Professional Skepticism Scale (HPSS): Autonomy, Self Esteem, Question Mind, Suspension of Judgement, Search for Knowledge, and Interpersonal Understanding. We compare the skepticism scores of two grouping variables which are: The students who have participated in professional ethical course (Sample 1) and the students who haven’t participated in professional ethical course (Sample 2). The results show that Sample 1 was more skeptical in terms of Self Esteem. On the other hand the difference between the two samples in skepticism score for the other five factors was found insignificant.